Pengaruh Product Knowledge, Product Quality, dan Brand Image terhadap Purchase Intention Produk Kosmetik Maybelline di Surabaya - Brilian Valentia Stevani; Sonja Andarini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to investigate and comprehend The Influence of Product Knowledge, Product Quality, and Brand Image on Purchase Intention of Maybelline cosmetic products in Surabaya. The Quantitative approach used in this study involves distributing questionnaires to 100 respondents. Multiple linear regression is used as the method of analysis using SPSS 26 For Windows. Three independent variables in this study, i.e. Product Knowledge, Product Quality, and Brand Image, as well as dependent variable, purchase Intention. The result of this study 1) Product Knowledge, Product Quality, and Brand Image simultaneously influence Purchase Intention of Maybelline cosmetic products in Surabaya. 2) Product Knowledge partially has a positive effect and significant effect on Purchase Intention of Maybelline cosmetic products in Surabaya. 3). Product Quality partially has a positive effect and significant effect on Purchase Intention of Maybelline cosmetic products in Surabaya. 4) Brand Image partially has a positive effect but not significant effect on Purchase Intention of Maybelline cosmetic products in Surabaya. Keywords: Product Knowledge, Product Quality, Brand Image, Purchase Intention